Crystallization of SiC and its effects on microstructure, hardness and toughness in TaC/SiC multilayer films. Issue 1 (January 2018) - Du, Suxuan; Zhang, Kan; Wen, Mao; Ren, Ping; Meng, Qingnan; Zhang, Yidan; Zheng, Weitao
Abstract: A series of TaC/SiC multilayer films with different SiC thicknesses (tSiC ) have been prepared by magnetron sputtering and their microstructure, hardness and toughness investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), atomic force microscopy (AFM), scanning electron microscopy (SEM) and nanoindentation. Results show that SiC crystallized and grew coherently with TaC layers at low tSiC (≤ 0.8 nm), resulting from the template effect of TaC layers. Maximum hardness and toughness of 46.06 GPa and 4.21 MPa m 1/2 were achieved at tSiC = 0.8 nm with good coherent interface. With further increasing of tSiC, SiC layers partially transformed to an amorphous structure and gradually lost their coherent interface, leading to a rapid drop in hardness and toughness. The crystallization of SiC layers and the coherent growth are required to achieve superhardness and high toughness in the TaC/SiC multilayers.